Use of cationic surfactant-xylenol orange indicator in metals complexometry by back-titration with EDTA. - Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Editora Unesp, 1996)
The interaction of the xilenol orange and commercial disinfectant containing itself cationic-surfactant allowed the use indicator up to pH 11 by back-titration with EDTA, and the determination of total or partial concentration of metallic ions samples using the same indicator at the highest pH range.
Keywords: cationic surfactant; complexometry titration of metals with EDTA; xilenol orange in basic medium